Motivational Factors and Learning Enthusiasm: A Multi-Level Analysis in Buddhist Sunday Schools in Wonogiri Regency - Santi Tritana; Hesti Sadtyadi; Novianti Novianti (AL-ISHLAH: Jurnal Pendidikan, 2025)
Buddhist Sunday Schools (Sekolah Minggu Buddha, SMB) face ongoing challenges in sustaining students’ learning enthusiasm across different educational levels. Understanding how motivation influences engagement is critical to improving instructional practices in these multi-level settings. This study employed a mixed-methods design to explore the relationship between motivational factors and learning enthusiasm among 38 students (18 elementary, 10 junior high, and 10 senior high) from three SMBs in Wonogiri, Indonesia. Data were gathered through questionnaires, classroom observations, and semi-structured interviews. The analysis revealed a clear developmental trend in motivational orientation. Elementary students were predominantly driven by extrinsic motivation (r = 0.85, p 0.05, R² = 0.72), junior high students demonstrated a balanced mix of extrinsic and intrinsic factors, while high school students were primarily intrinsically motivated (r = 0.82, p 0.05, R² = 0.67). These findings indicate that students' motivational profiles evolve with age and educational stage. The results highlight the importance of tailoring motivational strategies to students' developmental levels. Effective interventions may include age-appropriate curriculum design, interactive and experiential learning activities, and structured spiritual mentorship to foster both engagement and long-term spiritual growth. This study underscores the value of differentiated motivational approaches in SMB settings. Adapting instructional methods to align with students' motivational development can enhance learning enthusiasm and support meaningful participation in religious education.